Análise de SNPs do DNA mitocondrial em indivíduos residentes no estado do Espírito Santo para aplicação na Identificação Humana - Ambrosio, Isabela Brunelli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Human identification through DNA is one of the most revolutionary products of Modern Genetics, making it an indispensable tool in criminal investigation. This identification is based on the genetic profile of the individual, the combination of several markers inherited from their parents. The markers are generally differences in nuclear and DNA sequences between individuals (polymorphisms). In some cases, the analysis of nuclear DNA cannot be applied, the most successful alternative is the analysis of mitochondrial DNA (mtDNA). Mitochondria are intracellular organelles with a double membrane present on all nucleated mammalian cells with separate and distinct extrachromosomal genome nuclear genome, the mt DNA. Most laboratories use typing based mtDNA polymorphisms in the nucleotide sequence in the noncoding region (also known as the control region, the hypervariable or D-loop) of mtDNA. However, in some haplogrupos classification may not be possible based on only control data region. Thus, studies suggest the need for additional typing single nucleotide polymorphisms (SNPs) in other regions of mtDNA, especially in cases where it is not possible to differentiate individuals only by the analysis of hypervariable region. This study aimed to analyze, analyze thirty (30) SNPs of mtDNA in samples of unrelated individuals born and living in the State of Espírito Santo, allowing their classification in haplogroups and complementing the SNPs data of mtDNA control region achieved in previous work in the laboratory, for later use in forensic cases. A total of 100 samples, 19 were found haplogroups and the sample were classified according to its origin: 43% African, 30% European, 26% Native American, and 1% Asian. The haplogroup was found more L3 having African origin. Some samples of previous work could not be correctly classified only with the sequencing of the control region of mtDNA, after analysis of 30...

A identificação humana por meio do DNA constitui um dos produtos mais revolucionários da Genética Moderna, tornando-se uma ferramenta indispensável na investigação criminal. Essa identificação é baseada no perfil genético do indivíduo, pela combinação de diversos marcadores herdados de seus progenitores. Os marcadores são, geralmente,e diferenças nas sequências de DNA nuclear entre os indivíduos (polimorfismos). Em alguns casos, em que a análise do DNA nuclear não puder ser aplicada, a alternativa de maior sucesso é a análise do DNA mitocondrial (DNAmt). As mitocôndrias são organelas intracelulares de dupla membrana presentes em todas as células nucleadas de mamíferos, com genoma extracromossômico separado e distinto do genoma nuclear, o DNA mt. A maioria dos laboratórios que utilizam tipagem do DNAmt baseiam-se nos polimorfismos presentes na sequência de nucleotídeos na região não codificadora (também conhecida como região controle, hipervariável, ou D-loop) do DNAmt. No entanto, a classificação em alguns haplogrupos pode não ser possível com base em dados apenas da região controle. Assim, estudos sugerem a necessidade de tipagem adicional de polimorfismos de nucleotídeos únicos (SNPs) em outras regiões do DNAmt, em especial, nos casos onde não é possível diferenciar os indivíduos apenas pela análise da região hipervariável. Este trabalho teve como objetivo analisar, analisar 30 (trinta) SNPs do DNAmt em amostras de indivíduos não relacionados, nascidos e residentes no Estado do Espírito Santo, permitindo a classificação das mesmas em haplogrupos e complementando os dados de SNPs da região controle do DNAmt obtidos em trabalho anterior no laboratório, para posterior utilização em casos forense. De um total de 100 amostras, foram encontrados 19 haplogrupos e a população estudada foi classificada conforme sua origem em: 43% africana, 30% europeia...
Keywords: Análise de DNA; Mitocondria; Polimorfismo (Genetica); Genetica da população humana; Genetica forense; Forensic genetics